Anatomy of development: Concept, theory, and practice - Pattaniak, Bikram Keshari (London Routledge, 2025)
This book details the fundamentals of development studies by adopting a multi-disciplinary approach. It presents a balanced mix of economic, social, political, cultural and administrative premises of development and analyzes its theoretical and practical dimensions. It also provides insight into the role of the stakeholders of development in different sectors.